VERNALIZING PRE-TRANSPLANTS IMPROVED THE AGRONOMIC CHARACTERISTICS OF STRAWBERRY GENOTYPES UNDER TROPICAL CONDITIONS - Oviedo, Victoria Rossmary Santacruz (2020)
Strawberry plant yields improve if they accumulate a certain number of cold hours, which does not occur naturally under tropical and subtropical climatic conditions. This study evaluated the agronomic characteristics of potted transplants from 14 strawberry genotypes that had been subjected to vernalization treatment prior to planting in the field. The transplants were stored in a cold chamber at 5°C for 576 h. The genotypes used in the experiment were Camino Real, Festival, Florida Eliane, Sweet Charliefp, Sweet Charlie, Dover, IAC Guaraní, Corea, Early Bright, and hybrid clones Dover × Rosalinda1, Dover × Rosalinda4, Dover × Oso Grande, Dover × Esplendida, and Dover × Aichi. The 14 genotypes in the control group received no vernalization treatment. Each experimental unit consisted of 15 plants. A randomized complete blocks experimental design was used with a 14 × 2 factorial arrangement and three repetitions. Subjecting the strawberry transplants to the vernalization treatment had a significant effect on the total number of fruits per plant and total and commercial yield of fruits per plant, but there was no significant interaction between the factors and the evaluated yield and growth characteristics. Dover × Oso Grande, Florida Eliane, Camino Real, and Festival produced the greatest numbers of large fruits per plant. Vernalizing strawberry transplants increased the yield and the number of medium and small sized fruits per plant. The results showed that vernalization is a technique that could be used in tropical climate conditions to improve strawberry cultivation  productivity.